A novel variant in diaphanous homolog 1 (DIAPH1) as the cause of auditory neuropathy in a Chinese family. (June 2020) - Wu, Kan; Wang, Hongyang; Guan, Jing; Lan, Lan; Zhao, Cui; Zhang, Mengqian; Wang, Dayong; Wang, Qiuju
Abstract: Objectives: To determine the genetic cause of non-syndromic autosomal dominant deafness segregating in a Chinese Auditory neuropathy (AN) family. Introduction: AN is a genetically related rare disease characterized by sensorineural hearing loss and retention of hair cell function. Diaphanous Homolog 1 ( DIAPH1 ) is the causative gene of DFNA1. To date, no evidence has been detected to reveal the connection between gene DIAPH1 and AN. Material and methods: Audiological and imageological examinations, genome-wide linkage analysis, and whole exome sequencing (WES) were carried out on the family members. Results: In the 13-member branch of the family, 4 patients with preserved otoacoustic emission or cochlear microphonic and abnormal auditory brainstem responses were diagnosed with AN. Linkage analysis detected an interval with a LOD (log odds) score >4 on chr5:138.845–149.509 cM. Using WES we identified a novel frameshift variant c.3551_3552del (p.Glu1184AlafsTer11) in exon 26 of DIAPH1 located in the linkage region. The variant was co-segregated with hearing impairment phenotype in the family except 4 members below the average age of onset. We have found sufficient evidence conforming with the American College of Medical Genetics and Genomics Guideline to consider c.3551_3552del as the genetic cause of the family patients. Conclusion: It is the first report to expand DIAPH1 -related phenotypic spectrum to include AN. Our findings could facilitate the clinical diagnosis and genetic counselling for AN, especially for those with DIAPH1 variants.